Pain in chronic pancreatitis: the role of neuropathic pain mechanisms. Issue 11 (19th June 2008) - Drewes, A M; Krarup, A L; Detlefsen, S; Malmstrøm, M-L; Dimcevski, G; Funch-Jensen, P
Abstract : Pain mechanisms in patients with chronic pancreatitis are incompletely understood and probably multifactorial. Recently, evidence from experimental human pain research has indicated that in many of these patients pain processing in the central nervous system is abnormal and mimics that seen in neuropathic pain disorders. The current review focuses on several lines of evidence supporting this hypothesis. Hence, the spontaneous and postprandial pain in chronic pancreatitis may reflect the characteristic pain features seen in patients with neuropathic pain. Biochemical and histopathological findings in tissues from patients with chronic pancreatitis are similar to those observed in patients with other nerve fibre lesions. Experimental studies have shown that patients with chronic pancreatitis show signs of spinal hyper-excitability counter-balanced by segmental and descending inhibition. Changes in the brain with cortical reorganisation to gut stimulation and increased activity in specific electroencephalographic features characteristic for neuropathic pain are also seen in patients with chronic pancreatitis. Finally, principles involved in the treatment of pancreatic pain have many similarities with those recommended in neuropathic pain disorders. In conclusion, a mechanism-based understanding of pain in chronic pancreatitis may have important implications for the treatment.